Multiyear variability of ice concentration in the White Sea according to satellite data - V. N. Baklagin (Лëд и снег, 2023)
The objectives of this study were to analyze satellite data on the ice conditions in the White Sea available for the period 1979-2021 so that to identify statistically significant trends in closeness of ice during that period, and to establish spatial and temporal characteristics of the sea ice regime in this area. It was found that according to the satellite data a statistically significant negative trend (-0.34±0.11% year-1 at a significance level of 0.05) of the ice closeness changes was observed over the above period for all areas of the sea, which corresponds to the general tendency of reducing the area of the Arctic ice cover due to the global warming. However, contrary to the statements of J.C. Comiso, D.K. Perovich, M.C. Serreze, J. Streve, D. Notz that since the beginning of the XX century the reduction of the ice area in the Arctic Ocean accelerates, no tendency in decrease of mean annual values of the ice closeness for the White Sea was revealed. In addition, the results of the regression analysis showed a slight decrease in the absolute value of the trend from - 0.74±0.38% year-1 in 1979-1996 to -0.47±0.25% year-1 in 1997-2020. It is also shown that the results of a comparative analysis of two trends in the year-to-year variability of ice closeness in the White Sea: the first one obtained from the microwave radiometer data provided by the National Snow and Ice Data Center, and the second one revealed from data of advanced microwave scanning radiometers (the University of Bremen), are in good agreement with each other. The difference in the slope coefficients of the linear approximation is only 0.038% year-1 for the period 2002-2020. This is the important argument in support of using microwave radiometer data to determine trends in variability of ice closeness in the White Sea.